1972
DOI: 10.2307/523920
|View full text |Cite
|
Sign up to set email alerts
|

The Holy Ghost Fathers in Eastern Nigeria, 1885-1920: Observations on Missionary Strategy

Abstract: The Holy Ghost Fathers have been in Kastern Nigeria for about eighty-five years. Not until after the recent Nigeria-Biafra War has their influence been somewhat minimized. Arriving originally from France in 1885, the Roman Catholic missionaries, as we shall see later in this essay, exerted a considerable influence far out of proportion to their number. But despite that they had become a factor to be reckoned with ever since, their missionary activity has scarcely been studied systematically. One principal reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Another important aspect of mission education in Igbo society that is omitted in the book was the early education of Igbo girls and women. Historical studies by Omenka (, ), Ubah (, ), Nwabara (, ), Isichei (, ), Ayandele (, ), and Ekechi (, , ) and non‐historical works such as Okafor (), Kalu (), and Ilogu () have contributed to our understanding of Christian mission activities and their impact on the Igbo and their society.…”
Section: Religion and Formal Educationmentioning
confidence: 99%
“…Another important aspect of mission education in Igbo society that is omitted in the book was the early education of Igbo girls and women. Historical studies by Omenka (, ), Ubah (, ), Nwabara (, ), Isichei (, ), Ayandele (, ), and Ekechi (, , ) and non‐historical works such as Okafor (), Kalu (), and Ilogu () have contributed to our understanding of Christian mission activities and their impact on the Igbo and their society.…”
Section: Religion and Formal Educationmentioning
confidence: 99%
“…I have yet to locate O'Shea, and what I did find was a veritable absence of material on Irish involvement in British colonialism which, while unsurprising, spoke volumes. Re/ tracing colonialism in Nigeria, however, immediately brought me to the lengthy history of Irish religious missionization/colonization there (Ekechi, 1972). Because of the duration and extent of Irish religious presence/occupation in the region and the depth of their immersion in local life, this line of inquiry led quickly to the war in Biafra, and the involvement of Irish clergy in the war and famine aid campaign.…”
Section: Colonial Amnesiasmentioning
confidence: 99%
“…Recent studies have confirmed that missionaries disseminated education neither for its own sake nor to enable Africans to challenge colonial rule (Ajayi, 1965;Ayandele, 1966;Ekechi, 1972;Foster, 1965;Heyman, 1972;King, 1971;Wright, 1971). Nor can we make a distinction between the activities of European missionaries and their African proteges.…”
mentioning
confidence: 99%